FAMILY SUPPORT FOR PEOPLE WITH HIV AND AIDS (PLWHA) - Dewi Purnamawati; Nurfadhilah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
This study aims to describe family support for People Living with HIV and AIDS (PLWHA). This research is a quantitative descriptive study. The study was conducted at Puskesmas Bogor Tengah, Bogor. The population was PLWHA and the sample of 50 was taken randomly. Data were collected using a questionnaire that had been tested for validity and reliability. Data were analyzed descriptively. The results showed that the average age of respondents was 29.6 years, the average length of illness was 5.9 years, 86% were male, 42% had high school education, 76% were unmarried and 66% of PLWHA had insufficient family support such as lacked information support (49%), service support (45.1%), financial support (35.3%), appreciation support (33.3%), and emotional support (31.4%). Family support is needed to increase the resilience of PLWHA in improving their quality of life.